Epitope mapping and functional characterization of monoclonal antibodies against the tip-localized adhesions of CFA/I, CS17 and CS2 class 5 fimbriae of enterotoxigenic Escherichia coli - Sakina, Shahabudin (2013)
Enterotoxigenic Escherichia coIi(ETEC), a common cause of diarrhea among children in developing countries and in travelers, adheres to human small intestine via colonization factors (CFs) and secretes enterotoxins. Eight genetically related Class 5 fimbriae are prevalent ETEC CFs. Each is composed of a single tip-localized adhesin attached to a stalk of repeating major subunits. In this study, we performed epitope mapping and functional activity of total 28 monodonal antibodies (MAbs) against CfaE, CsbD and CotD, the tip adhesins of CFA/l, CS17 and CS2 fimbriae,respectively. To assess the MAb epitopes, panels of existing MAbs specific for each adhesin were tested for reactivity to the homologous adhesins, natural allelic variants and mutants by dot blot analysis and ELISA. Five antidscCfaE MAbs reacting to the CfaE adhesin domain, specifically recognized residues R67 and 11181, which are key residues in the receptor-binding pocket. Three anti-dscCsbD MAbs recognized residues 185, H144 or R181, all localized to the upper pole of CsbD. None of antidscCotD MAbs revealed specific epitope regions. We also tested the MAb reactivity to the heterologous Class 5 adhesins. The observed patterns of MAb cross-reactivity Included (1) exclusive reactivity to the homologous adheslns, (2) subclass-specific cross-reactivity, (3) class-specific cross-reactivity, and (4) selective cross-reactivity to certain heterologous adhesins. The MAb functional activity was measured in the minimum MAb concentration to inhibit hemagglutination of bovine erythrocytes by ETEC strains. Generally, lower MAb inhibition concentration correlates to higher MAb reactivity to the corresponding adhesin. However, the high ELISA reactivity of MAbs was not indicative to the functionality. Three MAbs showed class-wide reactivity, but none of the 28 MAbs showed class-wide hemagglutination inhibition. Collectively, our findings were the first step of fine epitope mapping of MAbs to the three representative Class S adhesins, and suggested diverse epitopes with unique MAb functionality on the three ETEC adhesins.